Russia's dead end : an insider's testimony from Gorbachev to Putin - Kovalev, A. A. (Andreĭ Anatolʹevich) (Potomac Books, an imprint of the University of Nebraska Press, 2017)
"An internal account of the political activities taking place inside the Kremlin from the fall of the USSR under the administration of Gorbachev to the future of Russia under Putin"--Provided by publisher.